2016
DOI: 10.1002/alr.21741
|View full text |Cite
|
Sign up to set email alerts
|

RESOLVE: bioabsorbable steroid‐eluting sinus implants for in‐office treatment of recurrent sinonasal polyposis after sinus surgery: 6‐month outcomes from a randomized, controlled, blinded study

Abstract: The symptomatic and endoscopic improvements observed confirm the efficacy of the steroid-eluting implant for in-office treatment of CRSwNP after ESS. These longer-term 6-month study results demonstrate that the steroid-eluting implant represents a durable, safe, and effective treatment strategy for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 21 publications
0
62
0
1
Order By: Relevance
“…Implanted SESs included the Intersect ENT Propel Mini or Contour, an unnamed Intersect ENT‒provided steroid‐eluting stent, SinuBand fluticasone propionate, and the Relieva Stratus MicroFlow Spacer . The sites of local implantation and delivery were ethmoid sinus cavity and frontal sinus ostia . A summary of the analyzed studies with their respective primary and secondary outcome variables are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implanted SESs included the Intersect ENT Propel Mini or Contour, an unnamed Intersect ENT‒provided steroid‐eluting stent, SinuBand fluticasone propionate, and the Relieva Stratus MicroFlow Spacer . The sites of local implantation and delivery were ethmoid sinus cavity and frontal sinus ostia . A summary of the analyzed studies with their respective primary and secondary outcome variables are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…All included studies in the quantitative analyses were industry‐sponsored RCTs. All 7 studies utilized intrapatient controls (using different sinuses in the same patient), except Forwith et al (sham surgery). These 7 studies prescribed a 10‐ or 14‐day course of antibiotics postoperatively for all subjects, with the exception of Forwith et al, who prescribed daily doses of steroid nasal spray.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have focused on patient-reported QOL outcomes with the use of this device, and the relative efficacy in the treatment of different phenotypes of CRS has not been analyzed in previous studies [6][7][8]12]. The goal of this study was to determine if a bioabsorbable steroid-eluting implant would have a differential effect on patient-reported QOL relative to the status of baseline eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the utility of adjuvant use of a bioabsorbable steroid-eluting implant in ESS have demonstrated its safety and clinical effectiveness in CRS patients in general [6][7][8]12]. However, it is unclear which patient groups are most likely to benefit from this technology.…”
Section: Introductionmentioning
confidence: 99%
“…At 6 months, the treated patients had statistically significant improvement in Nasal Obstruction Symptom Evaluation score (p = 0.021) and greater than 2-fold improvement in mean nasal obstruction score (p = 0.124). 17 The treatment Han et al 16 RESOLVE: a randomized, controlled, blinded study of bioabsorbable steroid -eluting sinus implants for in office treatment of recurrent sinonasal polyposis.…”
Section: Sinuva Clinical Studiesmentioning
confidence: 99%